Philosophy of Human-Centrism in the System of Anthropological Studies - Kremen, V. H; Ilin, V. V (Anthropological Measurements of Philosophical Research, 2022)
Purpose. The basis of the presented research is a philosophical and methodological analysis of the human-centrism concept as a new intellectual strategy of comprehending and understanding the prospects of human existence in a situation of information-digital reality, which provides for the consistent solution of the following problems: 1) to make an explication of the conceptual content and semantic loading of human-centrism in the discourses of social philosophy and philosophical anthropology; 2) to analyse the theoretical significance and methodological role of human-centrism in the information-digital reality; 3) to characterize the main parameters of the problematic field of human-centrism in overcoming the crisis of identity and preserving the system of universal human values. Theoretical basis. The objective logic of unfolding of the modern information-digital world transforms philosophical anthropology into a new level of comprehending the human existence. Human-centrism interacts with philosophical anthropology and evaluates it from the point of its metaphilosophical, axiological-existential and methodological content. The assertion of human-centrism is caused by the identity crisis in the context of civilizational transformations, which as a result of the cumulative effect of information technology have a powerful influence on all aspects of human life and thinking. The philosophy of human-centrism as a life-affirming factor determines the development and adaptation of human self-consciousness to the modern socio-cultural environment, determined by information and technological processes. Originality. It is substantiated that human-centrism as a new strategy of modern philosophical and anthropological discourses opens new cognition perspectives of the essence of human in the information-digital reality and contributes to the construction and implementation of new dimensions of identity in interaction with a qualitatively different level of world attitude. Conclusions. The assertion of information-digital reality gives rise to a new type of philosophical and anthropological paradigm, a qualitative manifestation of which is the theory and methodology of human-centrism. It is characterized by a modern level of philosophical reflection, which allows preserving and at the same time renewing the system of universal human values. On this basis, human-centrism is a way of complementarity of all aspects of human life, who reconstructs themselves in a situation of new anthropological dimensions.